ECONOMIC DEVELOPMENT OF NORWAY (World Bulletin of Management and Law, 2024)
The purpose of this article is to analyze the macroeconomic indicators of Norway for a certain period with the subsequent formation of critical conclusions about the current economic development of the country. In addition, the study will examine the dynamics of economic growth and highlight the main factors contributing to development. The inflation rate estimate will be based on the Fisher index, taking into account the GDP deflator and the consumer price index. It will also analyze the unemployment rate, the difference between exports and imports, and highlight the key factors slowing economic growth in Norway. Ultimately, recommendations will be made to improve the overall economic situation in a given country.